2018
DOI: 10.3390/diseases6030058
|View full text |Cite
|
Sign up to set email alerts
|

Action Observation in People with Parkinson’s Disease. A Motor–Cognitive Combined Approach for Motor Rehabilitation. A Preliminary Report

Abstract: The aim of this study was to assess the role of Action Observation (AO) to improve balance, gait, reduce falls, and to investigate the changes in P300 pattern. Five cognitively intact People with Parkinson’s disease (PwP) were enrolled in this prospective, quasi-experimental study to undergo a rehabilitation program of AO for gait and balance recovery of 60 min, three times a week for four weeks. The statistical analysis showed significant improvements for Unified Parkinson’s Disease Rating Scale (UPDRS) motor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…The implementation of training programs based on the observation of executed actions could allow the activation of motor representations and the reinforcement of old and/or new motor patterns learning, while modulating motivational processes in PD. Di Iorio et al (2018) have recently suggested that action observation is a “safe and feasible” rehabilitative exercise for improving balance, gait, and reducing falls in PD. Their positive findings, the simplicity of treatment, the lack of side effects, support our hypothesis of exploiting MNS, action observation and “somato-aesthetic empathy” to act on a motivational and behavioral level.…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of training programs based on the observation of executed actions could allow the activation of motor representations and the reinforcement of old and/or new motor patterns learning, while modulating motivational processes in PD. Di Iorio et al (2018) have recently suggested that action observation is a “safe and feasible” rehabilitative exercise for improving balance, gait, and reducing falls in PD. Their positive findings, the simplicity of treatment, the lack of side effects, support our hypothesis of exploiting MNS, action observation and “somato-aesthetic empathy” to act on a motivational and behavioral level.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies have further examined the role of AOT in PD rehabilitation, showing significant results in terms of improvement not only from the motor but also from the cognitive point of view. In a study by Di Iorio et al () in cognitively conserved patients with PD, the improvement in cognitive and motor performance (including FoG) thanks to AOT was correlated with a reduction in P300 latency duration (finding which points to changes in cortical activity). Another study (Caligiore et al, ) showed that long‐term AOT could also lead to cognitive improvement in PD patients if utilized within a dual task framework.…”
Section: Mirror Neurons and Neurodegenerative Diseasesmentioning
confidence: 93%
“…However, AO can be used as peripheral feedback and sensorimotor integration by modulating cortical plasticity and may provide them with convenient cues to enhance their motor function. Despite the small number of studies, this fact can be supported [ 29 , 30 , 31 ]. However, due to the diversity of interventions in these studies, it is unclear how the stimuli and the dose of interventions affected the outcomes.…”
Section: Introductionmentioning
confidence: 99%